2004
DOI: 10.1002/cncr.20568
|View full text |Cite
|
Sign up to set email alerts
|

The clinical value of tumor burden at diagnosis in Hodgkin lymphoma

Abstract: BACKGROUNDThe authors investigated the clinical role of tumor burden (TB) in patients with Hodgkin lymphoma, relating this parameter to most of the current clinical and prognostic factors and to the best predictive multifactorial models.METHODSThe volume of TB at diagnosis was measured directly from the initial staging computed tomography scans in 351 patients who were treated on standard protocols. The mean patient age was 34.0 years ± 16.4 years. Forty‐six patients had clinical Stage I disease, 201 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 26 publications
1
22
1
4
Order By: Relevance
“…Previous studies have demonstrated that total tumor burden measured using a CT scan can be a predictive tool for evaluating the curative potential of a treatment combination. (30,31) According to those studies, the treatment strategy might be decided dependent on the total tumor burden as well as the presence of bulky disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that total tumor burden measured using a CT scan can be a predictive tool for evaluating the curative potential of a treatment combination. (30,31) According to those studies, the treatment strategy might be decided dependent on the total tumor burden as well as the presence of bulky disease.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor burden also provides meaningful comparison between different treatment regimens, and has been shown to be accurate as an assessment of prognosis. An accurate assessment allows both physicians and patients to make better therapeutic choices earlier [17]. …”
Section: Introductionmentioning
confidence: 99%
“…In a prior study of HL patients treated on standard protocols, the mean tumor burden normalized to body surface area based on CT measurements was found to be largely superior to all prognostic models as a predictor of complete remission and survival [124,125]. Given the coverage of the entire body, metabolic volume determination may be a better surrogate for response and survival by representing overall tumor functionality.…”
Section: Prognostic Value Of Pet-derived Quantitative Metrics At Basementioning
confidence: 99%
“…Hodgkin lymphoma Tumor bulk is a significant negative prognostic factor in early-stage HL [113,[123][124][125]. However, not only the exact definition of tumor bulk remains a controversial topic but also an objective method to measure whole body tumor burden is yet to be established for a patient-tailored management.…”
Section: Prognostic Value Of Pet-derived Quantitative Metrics At Basementioning
confidence: 99%